2021
DOI: 10.3897/pharmacia.68.e65136
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ strategies to detect, resolve, and prevent DRPs in CKD patients

Abstract: Pharmacists have undergone obstacles in the process of detecting, resolving, and preventing CKD patients’ DRPs. Thus, optimal strategies were needed. A total of 19 articles were included based on the article searching process. Based on the articles, it can be concluded: The strategies of detecting DRPs in CKD patients were carried out through medication reconciliation and medication review. The outcomes of these strategies were the number of DRPs/patients and types of DRPs detected. Strategies to resolve and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…14 There are many studies conducted in patients with other clinical conditions that reported the frequency of DRPs either equal or different than our findings. 19,20 These differences are mostly due to the variation in the sample size, study design, age of the study population, extent of involvement by clinical pharmacist, polypharmacy and presence of other co-morbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…14 There are many studies conducted in patients with other clinical conditions that reported the frequency of DRPs either equal or different than our findings. 19,20 These differences are mostly due to the variation in the sample size, study design, age of the study population, extent of involvement by clinical pharmacist, polypharmacy and presence of other co-morbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) stands as a formidable global public health challenge, demanding timely identification and intervention to impede its progression [1][2][3][4][5]. Upon reaching the critical stage culminating in end-stage renal disease (ESRD), patients confront the necessity for kidney replacement therapies (KRT), encompassing hemodialysis (HD), peritoneal dialysis (PD), and kidney transplant (KT) [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and prevention of DRPs among patients with kidney dysfunction in developed countries has been made possible by the incorporation of clinical pharmacy services and the application of evidence-based guidelines [ 18 , 19 ]. This has led to a comprehensive and interdisciplinary approach to identify, prevent and manage DRPs in these patients [ 19 , 20 ]. In particular, pharmacist-led interventions have successfully identified and resolved DRPs in patients with kidney dysfunction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%